Discriminatory Ability of Lower-Extremity Peak Torque and Rate of Torque Development in the Identification of Older Women With Slow Gait Speed - Morcelli, Mary Hellen [UNESP]; LaRoche, Dain Patrick; Crozara, Luciano Fernandes; Marques, Nise Ribeiro [UNESP]; Hallal, Camilla Zamfolini; Goncalves, Mauro [UNESP]; Navega, Marcelo Tavella [UNESP] (Human Kinetics Publ Inc, 2018)
The aim was to compare torque and rate of torque development of lower limb muscles between older women with functional and slow gait speeds to determine which muscle group is the best predictor of functional gait speed, and to establish strength thresholds needed for functional walking speed. Torque and rate of torque development of hip, knee, and ankle muscles were measured in older women who were divided in 2 groups according to gait speed: slow gait speed (<1.22 m.s(-1)) and functional gait speed (1.22 m.s(-1)). For each muscle group, 3 maximal isometric contractions were performed, and peak torque and rate of torque development were recorded. Older women with slow gait speed had lower peak torque than older women with functional gait speed for hip extension (28%), knee flexion (15%), knee extension (14%), and plantar flexion (16%) (all Ps < .05). Older women with slow gait speed had lower peak rate of torque development for hip flexion (29%), hip extension (37%), knee flexion (34%), knee extension (33%), and plantar flexion (19%) (all Ps < .05). Knee extension peak rate of torque development and hip extension peak torque were the better predictors of functional gait speed with thresholds of 2.96 N.m.s(-1).kg(-1) and 1.26 N.m.kg(-1), respectively.
Keywords: hip; knee; ankle; mobility